PROCELOS eat local produce! - Ouédraogo, Jean-Pierre (Technical Centre for Agricultural and Rural Cooperation, 1991)
Jean-Pierre Ouedraogo is currently coordinating the PROCELOS programme at CILSS. For ten years previously he was with the National Cereals Office in Burkina Faso as executive manager implementing the national policy of making local cereals more...